Encapsulation of bioactive agent (Curcumin, Moringa) in electrospun nanofibers – Some insights into recent research trends. (2021) - Sundhari, D.; Dhineshbabu, N.R.; Sutha, S.; Raja Saravanan, M.E.
Abstract: As the epidemic of coronavirus disease (COVID-19) has spread rapidly, health organizations around the world has made wearing face mask obligatory to prevent the spread of the infections for the wellness of the society. As wearing face masks become a daily routine, the usage of cloth facemasks from textile fabric, is popular among the public. Since antiquity, textiles have been proven to be intertwined with human lives and the integrant of these crucial materials are fibers. Particularly, nanofiber fabrics manufactured by electrospinning have attracted attention, owing to the better filtration efficiency and breathability. In addition, the electrospinning process provide opportunities to fine tuning of the surface functionality through polymer chemistry and an encapsulation of bioactive agents in single step process. This review opens up a new horizon in possible textile applications especially, an active layer of bioactive agent (Curcumin and Moringa) loaded nanofibrous fabrics-based facemasks for day to day life.